Loading of Ce and n co-doped TiO2 composites onto modified shell powder synergism of adsorption and photocatalysis phytic acid removal: performance and mechanism - Zhang, Wei; Wang, Zheng; Shu, Jinkai; Wang, Aihe; Lin, Hai; Yan, Xuchao (Frontiers in Environmental Chemistry, 2025)
Phytic acid was investigated as an organophosphorus pollutant. Titanium dioxide (TiO2) doped with Ce and N was prepared using the sol-gel method and loaded onto a modified shell power to produce modified shell powder/Ce-N-TiO2 (Msp/CeNT). The combined effects of adsorption and photocatalysis on phytic acid were explored. The actual phytic acid degradation rate with the composite photocatalyst was higher than the sum of the adsorption removal rate of phytic acid using the modified shell powder and the photocatalytic degradation removal rate of phytic acid using the Ce-N-TiO2 photocatalyst. Msp/CeNT synergistically affected adsorption and photocatalytic degradation. The effects of different factors, such as reaction temperature, catalyst dosage, initial pH, stirring speed, and light intensity, on the combined effect were investigated. The results showed that the synergistic effect increases with the increase of light intensity. Increasing the reaction temperature, catalyst dosage, initial pH, and stirring speed first increased and then decreased the synergistic effect of the composite photocatalysts. Phytic acid (69.54%) was degraded within 4 h when the temperature, pH, catalyst dosage, stirring speed, and light intensity were 25 °C, 5, 1 g/L, 300 rpm, and 500 W, respectively. We investigated and prepared a composite photocatalytic material, developing a new theoretical method for degrading organophosphorus dissolved in water and providing a basis for treating lake eutrophication as a practical application.